A dual‐polarized low‐profile microstrip patch antenna with U‐ or M‐shaped feed network. Issue 6 (28th March 2019) - Liao, Dunwei; Wei, Feng; Zou, Xintong
Abstract: In this article, a dual‐polarized low‐profile microstrip patch antenna with U‐ or M‐shaped feed network is presented. The U‐ or M‐shaped feed network is printed on the same layer, which can achieve dual bands (5.3 and 5.8 GHz) and low profile (0.06 λg ). Dual polarizations and high isolation are realized by making use of a quasi‐cross‐shaped slot feeding. Moreover, the port isolation is better than 25 dB, and the antenna gain is above 8.4 dBi for the two ports. And the cross‐polarization levels in both E and H planes are better than ‐30 dB for the two polarization ports, respectively. The design is suitable for array application in MIMO system. Details of the proposed design and experimental results are presented and well agreed.